SIGNIFICANCE OF MINERALS AND ORE MINERALS AND ENRICHMENT TECHNOLOGIES - Xalikulova Xayat (Journals Park Publishing, 2022)
This article talks about the importance of minerals and ore minerals, their beneficiation methods and technologies. A mineral is a complex complex of various minerals. In addition, you can get detailed information about valuable components, useful and harmful additives, companion elements.
Keywords: Minerals, ore minerals, precious components, concentration